Assessment of Acoustic Quality in Classrooms Based on Measurements, Perception and Noise Control - Zannin, Paulo Henrique Trombetta; Zwirtes, Daniele Petri Zanardo; Passero, Carolina Reich Marcon (IntechOpen, 2012)
None